Application of Resilience Architecture in Buildings of Kumala Island Tourist Attraction - Sasputra , Lufianur; Hastiantti , RA Retno; Tjahja Prakasa , Darmansjah (International Conference of Innovation and Community Engagement, 2024)
The relocation of Indonesia’s capital city from Jakarta to East Kalimantan resulted in increased urbanization in East Kalimantan. The aim of relocating the capital city is to reduce the burden on Jakarta which is experiencing various problems, such as traffic jams, land subsidence, pollution, and an excessively high population burden. As a result, there has been an increase in the number of people migrating and returning to East Kalimantan. On the other hand, there is the potential of East Kalimantan which has natural resources that have not been developed optimally, including the tourism sector. One thing that is unique is Kumala Island as a tourist attraction which is located in the middle of the Mahakam River. Currently, the island still receives little attention in its development and improvement. This research will be conducted using observational research methods and directly analyzing the level of damage to buildings and their surrounding environment. It can be concluded that several buildings need to be rehabilitated using a resilience architecture approach to achieve building designs that are more resistant to challenges from environmental change and natural disasters. This approach not only focuses on the physical resilience of buildings and infrastructure, but also on environmental sustainability, adaptation to climate change, and the welfare of local communities. The final result of the research is a resilient tourist attraction design that is able to offer a safer and more comfortable experience for visitors, as well as support the sustainability of local ecosystems and cultures.